Computational and Mathematical Methods in Information Science and Engineering - Zhang, Wen; Xu, Xiaofeng; Wu, Jun; He, Kaijian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Nowadays, computational and mathematical methods provide effective tools for handling vast quantities of data and information in the fields of big data analytics, knowledge discovery and decision-making for solving complex problems in the world. The present reprint contains all of the articles accepted and published in the first edition of the Special Issue titled "Computational and Mathematical Methods in Information Science and Engineering". The objective of this Special Issue is to provide a channel through which members of the scientific community can exchange insights regarding recent advances in the theory and application of computational and mathematical methods in information science and engineering, with the long-term goal being to solve data-handling problems in practice. We hope that the papers published in this Special Issue will be considered impactful by the international scientific community and motivate further research into computational and mathematical methods that can solve complex problems in various fields and applications.